The leadership of Arequipa in the South Macro Regional context of Peru: A socioeconomic analysis of globalised space - Cuisano Marreros, Vladimir Richard (2015)
Arequipa is considered the second most important region of Peru after Lima and chief among the members of the South Macro Region. Arequipa radiates an area of influence throughout southern Peru, generating socioeconomic relations by multiple territorial scales. The overall objective of this research seeks to understand the territorial functionality of Arequipa and identify the factors that have allowed it to become the coordinating centre of the SMR. Furthermore, the methodology analysed the recent data from Gross Domestic Product, the Economically Active Population and population structure. Also, the Location Quotient is used to identify the productive vocation of each region of the SMR. Eventually, the development of networks which linking the south of Peru was studied.